P2M-WBF: STRATEGI MENINGKATKAN KONDISI FISIK ATLET SKI AIR DAN WAKEBOARD DKI JAKARTA - Uzizatun Maslikah; Fahmy Fachrezzy; Mansur Jauhari; Iwan Hermawan; Arga Nurcahya (Yayasan Education and Social Center, 2023)
P2M-WBF It is a community service program in the target area of ??the Faculty of Jakarta State University at the PSAWI Pengprov (Indonesian Water Ski and Wakeboard Association) DKI Jakarta. This Community Service aims to increase athletes' knowledge about improving the physicality of Water Skiing and Wakeboarding in achieving optimal performance. The method of carrying out the activity is the lecture method and instructors from DKI Jakarta PSAWI Pengprov who have qualifications in the field of Water Skiing and Wakeboard sports that are Nationally licensed and speakers who have licenses in the field of improving physical conditions. While the material that will be given in the implementation of community service consists of: 1) carrying out the pre-test, 2) Providing the main material for Improving Physical Conditions; 3) Providing practical materials; 4) Carrying out theoretical and practical evaluations. The objectives of this activity are: 1) As an effort to increase knowledge, understanding, and skills for Water Ski and Wakeboard athletes; 2) as an effort to improve the quality and human resources, especially for DKI Jakarta water ski and wakeboard athletes in obtaining optimal performance